Astrology in the crossfire: the stormy debate after the comet of 1577. Issue 2 (3rd April 2022) - Almási, Gábor
ABSTRACT: The new star of 1572 and the comet of 1577 had a major impact on the ways in which astronomical research developed in the late sixteenth and early seventeenth centuries. Behind this gradual but significant change there was an extended epistemological reform which placed increasing emphasis on reason and experience and strove to exclude arguments from Scripture and authority from scientific debate. This paper argues that the humanist debate on astrology after 1577, which was initiated by highly prestigious members of a supraconfessional Republic of Letters, can be seen as an element of this process. Unlike earlier detractors of astrology, these new critics chiefly employed philosophical and scientific arguments concerning the legitimation of the entire art. By analysing a variety of accounts, this paper will reveal how great and complex the stakes in the debate over astrology were. They concerned not only the crucial problem of predestination and God's interventionalism (hence also the possibility of miracles), but also the idea of science, the concept of the human mind, and ultimately the humanist ideal of the virtuous, rational, and responsible citizen.